Passive Participation in Collaborative Online Learning Activities: A Scoping Review of Research in Formal School Learning Settings - Choi, Hajeen; Hur, Jaesung (Online Learning, 2023)
This scoping review summarizes studies on passive participation in collaborative online learning activities that used computer-mediated communication tools in school settings. A total of 42 articles spanning about 20 years were explored. ERIC and three main journal indexes from Web of Science were used to locate articles. For each year searched, there were only one to five studies that investigated passive participation, indicating that not many researchers have examined this topic in general. Most studies used mixed methods and were conducted in higher education settings in asynchronous online discussions. Three terms have been used to discuss the notion of passive participation: lurking for read-only behavior, legitimate peripheral participation for low contribution, and free riding for no contribution. Studies on passive participation have mainly explored four topical areas: motivational factors and reasons, participation types and behavioral patterns, effect on learning outcomes, and pedagogical strategies for de-lurking. Most studies have investigated passive participation as one of the behavior patterns among various types of participation. A few studies have solely examined read-only behaviors. The notion of passive participation varies among researchers and should therefore be redefined. Overall, there have been few studies on the topic of passive participation and those that have been conducted reveal some inconsistencies in their findings, indicating the topic requires further investigation. Future studies on this topic are urgently needed due to the forced shift to online courses precipitated by the pandemic. While instructors are also responsible for supporting their learners in this unprecedented context, researchers should investigate ways to help instructors better understand passive participants and encourage active learner participation in collaborative online learning space.